Assessment of hydrogen sulfide innocuousness on Cavia porcellus (guinea pigs) cardiac tissue - Gómez Herreros, César (2016)
Introduction. Hydrogen sulfide (H2S) is toxic and lethal to mammals at high concentrations, but at low concentrations may be beneficial. Objective. Assessment of hydrogen sulfide harmlessness on Cavia porcellus (guinea pigs) cardiac tissue in vivo. Design. Experimental study. Setting. School of Medicine Pharmacology Laboratory, Universidad Nacional Mayor de San Marcos, Lima, Peru, and Experimental Surgery Unit at Instituto Nacional de Salud del Niño, Lima, Peru. Biological material: Twenty one Cavia porcellus (guinea pigs). Interventions. The experimental design considered three groups: 1) Clean air (control); 2) H2S at 80 ± 20 ppm (experimental, gaseous exposure); 3) Sevoflurane 1.5% (gold standard). Animals were placed in a hood where they were nebulized for twenty minutes; at the end of the exposure, the heart was withdrawn for histopathological study. Main outcome measures. Cardiac cell injury. Results. H2S exposure did not induce abnormalities; otherwise, exposure to sevoflurane showed moderate impairment in 3 of 7 heart tissues, but the result was not significant (p > 0.05) for this group. Conclusion. H2S at 80 ± 20 ppm was innocuous on Cavia porcellus tissue cardiac.